Determination Of Exhaust Gas Concentration Around The Exhaust Manifold Of A Petrol Engine - Ismail, Mohd Syaifuldin (Universiti Sains Malaysia, 2005)
Motor vehicle emissions are the leading cause of air pollution in Malaysia, and the Malaysia Department of Environment (MDOE) is looking for new ways to combat the problem. In 1996, MDOE introduced two regulations to control vehicle emissions, stipulating certain exhaust emission standards for diesel and gasoline vehicles. The regulations will require MDOE to conduct verification tests on the vehicles emissions. The MDOE submitted a request to the US-AEP Director in Malaysia for a Cal/EPA technical assistance team from the California Environmental Partnership to be deployed to Kuala Lumpur to help MDOE address their vehicle emissions problems. The MDOE submitted a request to the US-AEP Director in Malaysia for a Cal/EPA technical assistance team from the California Environmental Partnership to be deployed to Kuala Lumpur to help MDOE address their vehicle emissions problems. The two representatives from Cal/EPAís Air Resources Board (ARB) selected to serve on the team were in Kuala Lumpur from March 20 through March 30, 1998. The team attended meetings with MDOE to share ARBís experience with motor vehicle pollution control and standards enforcement. The team was asked to provide technical assistance to MDOE personnel in developing i) An emission measurement capability in a laboratory setting, ii) Documentation and procedures systems, and iii) An inspection and periodic checking system, including maintenance and monitoring systems for motor vehicles. Malaysia is motor vehicle program currently lacks enforcement of certification standards and any in-use inspection/maintenance program. The only currently operating program is a safety inspection and idle emissions test for vehicles used commercially (heavy-duty vehicles, buses, taxis, and other business vehicles). This program affects only about 10 percent of the total vehicle population. There is no inspection program for private vehicles and no enforcement of certification standards through either new or in-use vehicle compliance testing.